2017
DOI: 10.1097/dss.0000000000001079
|View full text |Cite
|
Sign up to set email alerts
|

Striae Distensae: Preventative and Therapeutic Modalities to Improve Aesthetic Appearance

Abstract: There are few randomized controlled trials evaluating the long-term efficacy and safety of various topical and energy-based devices. Based on clinical and anecdotal experience, both nonablative and ablative fractionated lasers have shown modest SD improvement compared with other treatment modalities (including Excimer laser, CuBr laser, pulsed dye laser, and 1,064-nm Nd:YAG laser). In the authors' experience, 1,540-nm nonablative fractionated laser is a worthy first-line modality for the treatment of SD. Futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 122 publications
0
29
1
4
Order By: Relevance
“…A previous review reported that 1540-nm nonablative fractionated laser was a worthy first-line modality for the treatment of SD, [ 3 ] based on clinical and anecdotal experience, which was inconsistent with our meta-analysis. On the one hand, our study indicated that bipolar radiofrequency was superior to laser treatment.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…A previous review reported that 1540-nm nonablative fractionated laser was a worthy first-line modality for the treatment of SD, [ 3 ] based on clinical and anecdotal experience, which was inconsistent with our meta-analysis. On the one hand, our study indicated that bipolar radiofrequency was superior to laser treatment.…”
Section: Discussioncontrasting
confidence: 66%
“…[ 2 ] SD generally appears along the cleavage lines in the abdomen, hips, thighs, and breasts, commonly developing during pubertal growth spurts and pregnancy, and associated with Cushing syndrome and oral or topical corticosteroid use. [ 3 ] The pathophysiological mechanism of SD involved in an inflammatory reaction and elastolysis arising from the release of elastase from mast cells. [ 2 , 4 ] Similar to scars, SD histologically is characterized by thinning of the overlying epidermis, loss of rete ridges, densely packed collagen bundles aligned parallel to the reticular dermis and atrophic skin.…”
Section: Introductionmentioning
confidence: 99%
“…Striae distensae alba typically appear as atrophic dermal scars where gaps are filled with new, disorganized collagen and elastin. 38 Striae may develop with topical corticosteroid overuse and hormonal changes affecting elastic fiber integrity in skin. 38 Treatments for striae and scarring include topical acids and retinoids, lasers, intense pulsed light, microneedling, fractionated radiofrequency microneedles, and chemical peels, to resurface the skin and trigger extracellular matrix turnover through a controlled wound repair process.…”
Section: Clinical Relevance Of Elastinmentioning
confidence: 99%
“… 38 Striae may develop with topical corticosteroid overuse and hormonal changes affecting elastic fiber integrity in skin. 38 Treatments for striae and scarring include topical acids and retinoids, lasers, intense pulsed light, microneedling, fractionated radiofrequency microneedles, and chemical peels, to resurface the skin and trigger extracellular matrix turnover through a controlled wound repair process. 32 , 38 However, scientific evidence of effective elastin repair and regeneration with these treatments is lacking compared with remodeling the collagen component of the skin.…”
Section: Clinical Relevance Of Elastinmentioning
confidence: 99%
See 1 more Smart Citation